The Effect of Aspect and Elevation on Critical Zone Architecture in the Reynolds Creek Critical Zone Observatory: A Seismic Refraction Study - Nielson, Travis; Bradford, John; Holbrook, W. Steven; Seyfried, Mark (Frontiers in Water, 2021)
In the northern hemisphere within snow-dominated mountainous watersheds north-facing slopes are commonly more deeply weathered than south-facing slopes. This has been attributed to a more persistent snowpack on the north facing aspects. A persistent snowpack releases its water into the subsurface in a single large pulse, which propagates the water deeper into the subsurface than the series of small pulses characteristic of the intermittent snowpack on south-facing slopes. Johnston Draw is an east-draining catchment in the Reynolds Creek Critical Zone Observatory, Idaho that spans a 300 m elevation gradient. The north-facing slope hosts a persistent snowpack that increases in volume up drainage, while the south-facing slope has intermittent snowpack throughout the drainage. We hypothesize that the largest difference in weathering depth between the two aspects will occur where the difference in snow accumulation between the aspects is also greatest. To test this hypothesis, we conducted four seismic refraction tomography surveys within Johnston Draw from inlet to outlet and perpendicular to drainage direction. From these measurements, we calculate the weathering zone thickness from the P-wave velocity profiles. We conclude that the maximum difference in weathering between aspects occurs ¾ of the way up the drainage from the outlet, where the difference in snow accumulation is highest. Above and below this point, the subsurface is more equally weathered and the snow accumulations are more similar. We also observed that the thickness of the weathering zone increased with decreasing elevation and interpret this to be related to the observed increase soil moisture at lower elevations. Our observations support the hypothesis that deeper snow accumulation leads to deeper weathering when all other variables are held equal. One caveat is the possibility that the denser vegetation contributes to deeper weathering on north-facing slopes via soil retention or higher rates of biological weathering.